A Modulatory Role for Clathrin Light Chain Phosphorylation in Golgi Membrane Protein Localization during Vegetative Growth and during the Mating Response of Saccharomyces cerevisiae - Chu, Diana S. (The American Society for Cell Biology, 1999)
The role of clathrin light chain phosphorylation in regulating clathrin function has been examined in Saccharomyces cerevisiae. The phosphorylation state of yeast clathrin light chain (Clc1p) in vivo was monitored by [(32)P]phosphate labeling and immunoprecipitation. Clc1p was phosphorylated in growing cells and also hyperphosphorylated upon activation of the mating response signal transduction pathway. Mating pheromone-stimulated hyperphosphorylation of Clc1p was dependent on the mating response signal transduction pathway MAP kinase Fus3p. Both basal and stimulated phosphorylation occurred exclusively on serines. Mutagenesis of Clc1p was used to map major phosphorylation sites to serines 52 and 112, but conversion of all 14 serines in Clc1p to alanines [S(all)A] was necessary to eliminate phosphorylation. Cells expressing the S(all)A mutant Clc1p displayed no defects in Clc1p binding to clathrin heavy chain, clathrin trimer stability, sorting of a soluble vacuolar protein, or receptor-mediated endocytosis of mating pheromone. However, the trans-Golgi network membrane protein Kex2p was not optimally localized in mutant cells. Furthermore, pheromone treatment exacerbated the Kex2p localization defect and caused a corresponding defect in Kex2p-mediated maturation of the α-factor precursor. The results reveal a novel requirement for clathrin during the mating response and suggest that phosphorylation of the light chain subunit modulates the activity of clathrin at the trans-Golgi network.